The AhR/IL-22 axis in chronic gut inflammation: unraveling mechanisms and therapeutic prospects - Kang, Huimin; Chen, Zheng; Wang, Baodong; Chen, Zhiyun (Frontiers in Immunology, 2025)
Chronic inflammatory bowel diseases, including Crohn’s disease (CD), ulcerative colitis (UC), and post-infectious irritable bowel syndrome (PI-IBS), are characterized by immune-mediated intestinal inflammation and epithelial barrier dysfunction. Research indicates that the aryl hydrocarbon receptor (AhR)/interleukin-22 (IL-22) pathway is critical for intestinal homeostasis. This pathway can be activated by ligands from dietary and microbial sources (such as tryptophan metabolites), and AhR signaling in immune cells (particularly type 3 innate lymphoid cells (ILC3s) and T cells) is the primary driver of IL-22 production. IL-22 protects the intestinal barrier and regulates inflammatory responses by promoting epithelial repair, enhancing mucus and antimicrobial defenses, and strengthening tight junctions. Dysregulation of this pathway plays a key role in the pathogenesis of chronic intestinal inflammation, leading to exacerbated inflammatory processes and mucosal damage. Given its central role in barrier defense and repair, targeting the AhR/IL-22 pathway has emerged as a novel therapeutic direction for restoring intestinal homeostasis. This review summarizes the mechanisms of action of this pathway in chronic intestinal inflammation and explores its potential as a novel therapeutic target.